PERANCANGAN APLIKASI CHAT TRANSLATOR BERBASIS DESKTOP UNTUK KOMUNIKASI DUA BAHASA DALAM JARINGAN KOMPUTER - Prasetya, Pradana Nur; Wintolo, Hero; Retnowati, Nurcahyani Dewi (Compiler, 2014)
One way of written communication is to send a message to the others. With the current technological developments, written communication can be supported by the computer and internet media so that messages sent can be delivered to target internet users in a short time and geographical distance is no longer a barrier of communication. In communicating between countries is often used in English, but that will be an obstacle when the language used to write the message was not understood by the other person and vice versa. Seeing this condition, then there needs to be an alternative media to overcome these obstacles. One of them is to design a bilingual (Indonesian-English) chat translator application. The system was created using Delphi 7 as a programming language and Oracle as Indonesian and English vocabulary storage database. Through this system, users can send messages using Indonesian or English and receive messages according to language used. The result from the design of this application indicates that the application is able to translate the text that is sent into the appropriate language which is controlled by interlocutors. So it can be a solution to communicate although with different language. However, the ability of the translator is very dependent on the current record in the dictionary table, so the translation can be developed in subsequent research to be more complete and better.